Mathematical modeling of heat and electromagnetic processes when determining current capacity in cable lines - Ekaterina Navalikhina; Natalia Trufanova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Ensuring performance and reliability of high-voltage cable lines laid in underground conduits, when designing and operating in limited heat exchange with the environment, it is impossible without a thorough understanding of heat and mass transfer in a duct considering alternating electromagnetic field and induced currents in metal screens realized in cable lines. The study focuses on solution of a collaborative problem of heat and mass transfer and electric and magneto dynamics arising in cable lines laid in underground cable channel under natural convection considering radiation energy and induced electromagnetic fields. The main aim of the study is to develop two-dimensional steady-state mathematical models of heat and mass transfer in natural convection considering electro- and magneto dynamics occurring in cable ducts to determine the rational value ??of current load and to ensure safe operation of the power cables. The methods used in the study: In order to solve the collaborative problem the authors used the theory of heat and mass transfer and electric and magneto dynamics, methods of mathematical modeling. Numerical simulation was carried out using the finite element method in modern engineering packages. The results: The authors solved the joint task of heat and mass transfer and electrodynamics and determined the temperature fields considering the additional heat generation in metal screens of power cables, arising due to the induced currents. The contribution of heat loss due to the induced currents in the cable shield into the overall heat balance of loaded cables was estimated. The paper introduces the recommendations for the largest bandwidth of cable lines depending on the ambient temperature.